Evaluation of families of crack users in relation to support groups - Maria de Lourdes Custódio Duarte; Leticia Passos Pereira; Juliana de Carvalho; Agnes Olschowsky
ABSTRACT Objective: to evaluate the perception of the relatives of crack users in relation to the support groups offered to this population in a Psychosocial Care Center for Alcohol and Drugs in the South of Brazil. Method: the fourth-generation theoretical framework was used for evaluation, having as methodological device the hermeneutical-dialectic circle. Data collection occurred through 500 hours of observations and interviews with 12 relatives of crack users, and the comparative constant method was used in the analysis, generating the "family group" unit of meaning. Results: this group was regarded by the family members as a space for guidance on the management of users in their home environment. They reported the need for a basic structure to conduct the groups, greater duration of the meetings, confidentiality of information and diversity of timetables. Final considerations: investment in education and training of nursing professionals focused on group care is suggested to the education institutions.